Great Power Politics and The Fourth Industrial Revolution: The Geo-Economics of Technological Sovereignty - Mukhtar Imam (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2023)
The Fourth Industrial Revolution (4IR) is reshaping global power dynamics through technological innovations such as artificial intelligence (AI), blockchain, and the Internet of Things (IoT). This paper explores the geopolitical implications of 4IR, particularly focusing on the concept of technological sovereignty and its impact on great power politics. As nations compete for technological supremacy, their strategies for achieving and maintaining control over critical technologies have become central to both national security and economic policies. This study adopts a qualitative research approach, employing case study analysis to examine the technological strategies of leading global powers, including the United States, China, and the European Union. Additionally, document analysis is used to explore policy reports and academic literature related to technological sovereignty, 4IR, and geopolitical rivalries. Thematic and comparative analyses are utilized to identify key patterns in the strategies of these powers, highlighting the intersection of technological competition, national security, and economic strategies. The findings of this research underscore the importance of technological sovereignty in the context of 4IR and provide insights into how nations navigate the complex terrain of global technological leadership.